The cognitive neuroscience of humor - Kennison, Shelia M. (American Psychological Association, 2020)
"In this innovative book, cognitive psychologist Shelia M. Kennison presents a rich overview of research on how the human brain works when processing humor, drawing on the new and sophisticated brain-imaging technologies that have enabled researchers and health professionals to expand their knowledge about how the brain works under different conditions. Kennison examines how humor is involved in cognition and memory, human development, and overall mental and physical health. Studies show that comprehending humor involves numerous regions throughout the brain and leads to physiological changes in the brain and body, which are beneficial for health. In contrast, humor deficits are observed in cases of normal aging, brain damage resulting from traumatic brain injury or disease, and developmental disorders such as autism spectrum disorder. Readers will gain a fundamental understanding of the biological basis of humor"--